Tumor stage, tumor site and HPV dependent correlation of perfusion CT parameters and [18F]-FDG uptake in head and neck squamous cell carcinoma. Issue 1 (October 2015) - Nesteruk, Marta; Lang, Stephanie; Veit-Haibach, Patrick; Studer, Gabriela; Stieb, Sonja; Glatz, Stefan; Hemmatazad, Hossein; Ikenberg, Kristian; Huber, Gerhard; Pruschy, Martin; Guckenberger, Matthias; Klöck, Stephan; et al.
Abstract: Background and purpose: This study investigated whether tumor perfusion, FDG uptake and their correlation depend on tumor stage, site and HPV in head and neck cancer. Material and methods: 41/55 eligible patients with integrated FDG-PET/perfusion CT from 2 prospective studies were assessed. A GTV CT and GTV PET were created. Perfusion maps were calculated using singular value decomposition method. Blood volume (BV), blood flow (BF), mean transit time (MTT) and standardized uptake value (SUV) in the tumor were compared to the surrounding tissue using Wilcoxon test and Spearman correlation of perfusion and SUVmean in the tumor was studied ( p  = 0.05). Results: Perfusion parameters were significantly increased in the GTV CT of advanced tumors in comparison to the surrounding soft tissue ( p  < 0.01). Oral cavity and oropharyngeal cancer showed a higher BF than laryngeal cancer ( p  < 0.04). No correlation between perfusion and SUVmean was found, however SUVmean correlated significantly with BF for the HPV-positive tumors ( r  = 0.86, p  = 0.04) and with BV for the oropharyngeal cancer ( r  = 0.63, p  = 0.05). Conclusion: Tumor stage, site and HPV are associated with different perfusion or combined perfusion/SUV signatures. Further studies are needed to investigate if these signatures co-determine clinical outcome.